Creating an AI Powered VR Simulation Platform for Social Work Skill Development. - Lanzieri, Nicholas; Dempsey, Anne; Olsen, Alvaro F.; Samelson, Henry; Plass, Jan L. (Journal of Technology in Human Services)
Virtual reality (VR) technology-based simulations have increasingly gained traction within social work education to teach clinical practice skills. Engaging with a virtual client helps social work students apply evidence-based interventions and skill sets. Acknowledging the strengths and limitations of currently available technology-based simulation, one school of social work, in collaboration with simulation and artificial intelligence (AI) engineering colleagues, aims to enhance VR-based simulation by integrating AI capabilities. This conceptual paper will describe the process and steps in creating that VR simulation platform, which was an interprofessional collaboration between social work educators, researchers, technologists, and engineers to design AI technology that students will interact with both verbally and textually. The paper will also review the iterative process that shaped the scenarios and interventions for clinical social work skill development. Additionally, next steps and their implications for social work education and practice will be discussed.